Literature Review Pipe Stress Analysis In Piping System - Pradipta, Nanang K.; Feriyanto, Dafit; Fitri, Muhamad (Universitas Pahlawan Tuanku Tambusai, 2025)
Piping systems are a major component in oil and gas processing facilities in Indonesia. With piping usage increasing every year, safety is a critical priority to avoid fatalities and losses due to piping damage. In order to ensure safety and reliability, a thorough analysis of piping stress analysis is required at design and operation stages. Piping stress analysis aims to assess the risk of stresses arising from various factors, including changes in temperature, internal pressure, and external environmental conditions. This study conducted a literature review of 51 international journals published between 2014 and 2024, focusing on factors that affect piping stresses analysis such as force loads, pipe support, piping layout, vibration, earthquake, and cryogenic service conditions. Based on this study, it was found that force load pressure & temperature, determining pipeline layout, pipe support location and vibration have a impact on pipe stress distribution, which in turn affects piping reliability and service life. Analysis using software such as CAESAR II proved effective in identifying critical areas on the piping and ensuring that the system performs in accordance with established safety standards. The review shows that piping stress analysis not only maintains safe operational limits but also improves piping reliability. With proper application of stress analysis, the risk of failure can be minimized, and the service life and reliability of the pipeline system increased. This application is important to maintain production continuity and minimize potential losses due to damage to the piping infrastructure. Keywords: Loads, Pipe Stress Analysis, Piping System, Piping Layout, Pipe Support